Flexible manipulators : modeling, analysis and optimum design. - Gao, Yanqing (Intelligent systems series., 2012)
The Intelligent Systems Series comprises titles that present state-of-the-art knowledge and the latest advances in intelligent systems. Its scope includes theoretical studies, design methods, and real-world implementations and applications. Flexible manipulators play a critical role in applications in a diverse range of fields, such as construction automation, environmental applications, and space engineering. Due to the complexity of the link deformation and dynamics, the research effort on accurate modeling and high performance control of flexible manipulators has increased dramatically in recent years. This book presents analysis, data and insights that will of particular use for researchers and engineers working on the optimization and control of robotic manipulators and automation systems. Government and industry groups have specifically stressed the importance of innovation in robotics, manufacturing automation, and control systems for maintaining innovation and high-value-added manufacturing Discusses the latest research on the quantitative effects of size, shape, mass distribution, tip load, on the dynamics and operational performance of flexible manipulators Presents unique analyses critical to the effective modeling and optimization of manipulators: hard to find data unavailable elsewhere.